Kinetic and isotherm studies on the adsorption of tenuazonic acid from fruit juice using inactivated LAB. (May 2018) - Liu, Bei; Ge, Na; Peng, Bangzhu; Pan, Siyi
Abstract: Tenuazonic acid is a fungal secondary metabolite that is produced by a number of Alternaria species and is therefore a natural contaminant of food and feed samples. The aim of this study was to investigate the adsorption kinetics and isotherms of tenuazonic acid (TeA) from citrus juice using inactivated lactic acid bacteria (LAB). The results showed that inactivated LAB-20023 could significantly reduce TeA from contaminated fruit juice. The kinetic models indicated that the biosorption process of TeA onto inactivated cells from fruit juice obeys a pseudo-second-order model rather than a pseudo-first-order kinetic model at all studied temperatures and initial concentrations. The equilibrium data were fitted to Langmuir and Freundlich isotherm models, and the results showed that the adsorption equilibrium was best described by the Freundlich isotherm. Highlights: Inactivated LAB-20023 could significantly reduce TeA from contaminated fruit juice. Biosorption process of TeA onto inactivated cells obeys a pseudo-second-order model. Adsorption equilibrium was best described by Freundlich isotherm.